The Effect of Geoclimatic Factors on the Distribution of Paracoccidioidomycosis in Mato Grosso do Sul, Brazil - Larissa Rodrigues Fabris; Nathan Guilherme de Oliveira; Bruna Eduarda Bortolomai; Lavínia Cássia Ferreira Batista; Marcos Henrique Sobral; Alisson André Ribeiro; Ursulla Vilella Andrade; Antonio Conceição Paranhos Filho; Lídia Raquel de Carvalho; Ida Maria Foschiani Dias Baptista; Rinaldo Poncio Mendes; Anamaria Mello Miranda Paniago (Journal of Fungi, 2024)
The incidence of paracoccidioidomycosis (PCM) varies in Latin America, and it is influenced by environmental factors. This study evaluated the distribution of PCM acute/subacute form (AF) cases and their correlation with geoclimatic factors in the Mato Grosso do Sul (MS) state. The study included 81 patients diagnosed with the PCM/AF at the University Hospital of the Federal University of Mato Grosso do Sul between January 1980 and February 2022. Geographic coordinates, health microregion of patient’s residence, compensated average temperature, relative air humidity (RH), El Niño Southern Oscillation (ENSO), and average global temperature were analyzed. The highest incidence was observed in the Aquidauana (7/100,000 inhabitants), while Campo Grande, the state’s capital, had the highest number (n = 34; 42.4%) and density (4.4 cases/km2) of cases. The number of cases increased during extended periods of the El Niño phenomenon. A positive correlation was found between higher RH and PCM/AF cases. Most PCM/AF cases were found in areas with loamy soils and RH ranging from 60.8 to 73.6%. In MS, the health microregions of PCM/AF patients are characterized by deforestation for agricultural and pasture use, coupled with loamy soils and specific climatic phenomena leading to higher soil humidity.